Indonesian Karst Museum As A Media And Source Of Development Of Historical Materials In Preaksara - Irawan, Dicky; Isawati, Isawati; Kurniawan, Dadan Adi (PAEDAGOGIA, 2020)
This study aims to explain: the background of the establishment of the Indonesian karst museum; Collection of Indonesian karst museums related to historical material for the Praaksara period; The relevance of the Indonesian karst museum as a medium and source of historical material development for class X SMA students on the topic of the Praaksara period. This study used a qualitative method with a descriptive approach. The data in this study started from informants, places, documents. The results showed that in the karst landscape of Mount Sewu, there were artifacts from past lives that needed attention and preservation. Collection of Indonesian Karst Museum related to pre-literary historical material includes: Replicas of Human Shell Songs and Keplek Songs in Pacitan. Replication of the Pawon Human Skeleton. Painting on the walls of the Muna karst area in Southeast Sulawesi. Replication of Homo floresiensis skeleton in Liang Bua Cave; The Indonesian Karst Museum is relevant to be used as a medium and source of historical learning in the basic competence of analyzing the similarities and differences between ancient Indonesian people and the world and modern humans in the physical aspect.